Corporate Governance, Globalization and Firm Performance: A Case of Nepal - Joshi, Arya; Byahut, Bikash; Sharma, Binita; Pandey, Prakash (Nepalese Journal of Finance, 2025)
This study examines the corporate governance, globalization and firm performance in the context of Nepalese commercial banks. Return on assets and return on equity are selected as the dependent variables. The selected independent variables are board size, audit committee size, number of board meeting, independent director, female board member and foreign ownership. The study is based on secondary data of 10 Nepalese commercial banks with 100 observations for the period from 2014/15 to 2023/24. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of corporate governance, globalization and firm performance in the context of Nepalese commercial banks. The study showed that board size has a positive impact on return on assets and return on equity. It indicates that larger the board size, higher would be the return on assets and return on equity. Similarly, audit committee size has a positive impact on return on assets and return on equity. It indicates that increase in audit committee size leads to increase in return on assets and return on equity. Likewise, number of board meetings have positive impact on return on assets and return on equity. It indicates that increase in number of board meetings lead to increase in return on assets and return on equity. Further, independent director has a positive impact on return on assets and return on equity. It indicates that increase in independent director leads to increase in return on assets and return on equity. In addition, female board member has a positive impact on return on assets and return on equity. It indicates that higher the female in board, higher would be the return on assets and return on equity. Moreover, foreign ownership has a positive impact on return on assets and return on equity. It indicates that increase in foreign ownership leads to increase in return on assets and return on equity.